The Effect of Self-care Education on Selfefficacy and Happiness of Elderly Women with Urinary Incontinence: A Randomized Controlled Trial - Sadeghi Moghimi, Elham; GHodsbin, Farba; Rambod, Masumeh (International Journal of Psychosocial Rehabilitation, 2020)
Medical and health-related progressions have caused not only the world’s population but the population in our country to live longer. Among the elderly’s problems, urinary problems are common among 65-year-old and older patients. One of the most significant urinary problems among the elderly is urinary incontinence. Due to cultural, social, and anatomical conditions, women are more prone to affliction to this disease. This disease can influence the patients’ daily routine activities, self-efficacy, and psychological health and happiness and lead to interferences with their self-efficacy and fulfillment. Thus, this study was conducted aiming at the investigation of the effect of self-care education on the elderly women’s self-efficacy and happiness suffering from urinary incontinence. This clinical investigation was done on 64 elderly women with urinary incontinence referring to Jahandidegan Center in Shiraz in 2018. The samples were included in the study by convenience sampling and divided into two interventions (n= 32) and control (n= 32) groups using simple random sampling. In the intervention group, the self-care education program was done in five 60-minutes sessions in the form of cooperative learning and lecturing two days a week but there was no interference in the activities of the control group. For the participants in the two groups, the Brome Pelvic floor muscle exercises self-care scale, chronic diseases self-care scale, and Oxford happiness questionnaire was completed in threetime intervals of before, immediately after, and two months after the intervention. Based on the obtained results, the mean score for self-efficacy pelvic floor muscle exercise scale and self-care scale in chronic diseases in the intervention group was meaningfully higher than that of the control group (P<0/001) immediately and two months after the intervention. Also, in the intervention group, these scores had a significant increase over time (P<0/001), while in the control group the increase in these scores over time has not been meaningful. The difference of happiness scores between the two groups, by considering the effect of the group alone, has not been meaningful (P=0/530), but the changes process is meaningful with regard to considering two factors of time and group (P<0/001). Self-care education, as a complement method can cause an increase in self-care and happiness on elderly women with urinary incontinence.